Prolonged Zika Virus RNA Detection in Semen of Immunosuppressed Patient - Christina Petridou; David Bonsall; Aleem Ahmed; Mark Roberts; Carolyn Bell; Mariateresa de Cesare; Rory Bowden; Victoria Graham; Daniel Bailey; Andrew Simpson; Emma Aarons (Emerging Infectious Diseases, 2019)
Zika virus RNA has been detected in semen samples collected <370 days after symptom onset. We report unusual persistence of Zika virus RNA in semen, confirmed by sequencing at 515 days after symptom onset and detectable for >900 days, in a patient with immunosuppression.